Analytical assessment of the features of composing the thematic map on the example of the mapping work "Agriculture of Ukraine" - Karas, I.; Kotkova, T.; Drebot, O.; Khudrik, A.; Yaremenko, O. (Land Management, Cadastre and Land Monitoring, 2023)
Cartography as a science distinguishes several different concepts that determine the practical scope of application of a cartographic work. One of the main concepts of cartography is language, which characterizes a map as a special text written using conventional signs, while the map conveys real reality, objects and natural environment. According to our research, the "Agriculture of Ukraine" map was analyzed in the following areas: structural elements of the map; elements of map content; methods of cartographic representation and thematic classification. The analyzed map has all structural elements: cartographic image, mathematical basis, legend, additional data and auxiliary equipment. During a detailed analysis of such a map element as a cartographic image, all thematic components of the map’s content were distributed among the following blocks: mapping objects; objects by visual perception; nature of distribution of objects; mapping indicators; mapping units. It was also established that the following methods of cartographic representation were used when composing the map, in particular, the method of localized icons, the method of linear icons, the method of areas, and the method of map diagrams. In general, the analytical study of the map "Agriculture of Ukraine" made it possible to fully evaluate this cartographic work from the point of view of the linguistic concept of cartography. Key words: map, content, constituent elements of the map, methods of cartographic representation, language concept of the map.